Estimating regime dependent fiscal spillover effects in a monetary union - Vanessa Kunzmann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2023)
I estimate regime-dependent spillover effects from government spending shocks across the members of the European Monetary Union (EMU). I use panel regressions for a total of 14 EMU economies from 1997 to 2022. Government spending shocks are defined by unexpected innovations to forecast predictions of government purchases, similar to Auerbach and Gorodnichenko (2013). However, In contrast to business cycle dependence, I investigate the quantitative impact of different fiscal policy regimes of the targeted country, the country of origin, and the monetary union on the spillover multipliers. Thereby, I allow fiscal and monetary policy to follow a twostate Markov Switching process characterizing an active and a passive regime as in Leeper (1991). Thus, governments differ in their debt reduction efforts to satisfy their budget constraint and monetary policy varies between inflation targeting and restrained price level determination. I find that spillover multipliers are highly regime-dependent, with positive and significant effects when the targeted country is active and the country of origin is passive. These effects are consistent but even larger for members with a high level of debt. However, results suggest that the importance of union-wide fiscal behavior and that of the central bank matters more for highly indebted countries. Thus, the interest rate channel is gaining relevance when debt is high.
Keywords: F41; F42; F45; E62; C2; 330; Fiscal Policy; Fiscal Spillovers; Fiscal Multiplier; Multiplier; European Monetary Union; Regime Switching; Fiscal Policy Rules; Monetary-Fiscal Interaction